Application of Bottom Ash Derived from Livestock Manure Combustion-Improved Soil Physicochemical Properties and Nutrient Uptake of Creeping Bentgrass - Young-Sun Kim; Seung-Jae Lim; Geung-Joo Lee (Horticulturae)
This experiment examined the effects of blending bottom ash produced after combusting dry livestock manure (BACL, 2–4 mm particle) as a soil amendment on the physicochemical properties of the root zone and growth response of creeping bentgrass in sandy soil. The treatments were designed as follows: control [100% sand], 3% BACL (3% BACL + 97% sand), 5% BACL (5% BACL + 95% sand), 7% BACL (7% BACL + 93% sand), and 10% BACL (10% BACL + 90% sand). Although BACL improved the soil physical properties, such as the capillary porosity, total porosity, and hydraulic conductivity, it reduced the cation exchangeable capacity. The BACL treatments increased the pH, EC, Av-P2O5, and Ex-K compared to the control. The turf color index, chlorophyll content, shoot length, clipping yield, and shoot dry weight after the BACL treatments were similar to the control. The growth and nutrient uptake of the roots in the BACL treatment were higher than those of the control. The BACL application amount was positively correlated with the capillary porosity and total porosity of the root zone (p ≤ 0.01) and with the growth and nutrient levels of the roots (p ≤ 0.05). These results suggest that applying BACL as a soil amendment enhanced the uptake of phosphorus and potassium in the roots of creeping bentgrass by improving the soil porosity in the root zone and by supplying phosphate and potassium.